Real Subsumption of Art to Capitalist Technical Reproducibility. Walter Benjamin and Bolívar Echeverría on Technology, Politics and Utopia under Capital - Monroy, Javier Gómez (Simmel Studies)

(untitled) (Edizioni ETS, 2023)
The objective of the present article is to analyse the examination carried out by Walter Benjamin on the transformation of art and the aesthetic experience in his work The Work of Art in the Age of its Mechanical Reproducibility. The analysis will be conducted departing from Bolivar Echeverría’s reception of Benjamin’s essay -that is informed by Karl Marx’s Theory of Subsumption- with the aim of precising and potentiating Benjamin’s critique to capitalist technology and stimulating the discussion on the post-capitalist technological alternatives. In addition to presenting the essential ideas of Benjamin’s argument on the modern technique of artistic production and the modern technique of production of goods in general, alternating them with Echeverría’s interpretations in which he remarks the critical utopian potential within them, the critical conceptual convergence between Walter Benjamin and Karl Marx around the analysis of the essence of modern technique and its historicity, is presented.